The economic cost of foreign exchange for South Africa - Harberger, Arnold C.; Jenkins, Glenn P.; Kuo, Chunyan; Mphahlele, M. Benjamin (Economic Society of South Africa, 2003)
IN ECONOMIC COST BENEFIT ANALYSIS there is a need to choose a numéraire in which all costs and benefits are evaluated. In recent years the most common practice has been to express all costs and benefits in terms of domestic currency at the domestic price level. When this numéraire is chosen it is necessary to adjust all transactions that are made with international traded goods and involve foreign exchange to account for the divergence that arise between the financial cost of foreign exchange and its economic value. The purpose of this paper is to develop an analytical framework that will enable us to estimate the economic cost of foreign exchange for South Africa.
Keywords: cost-benefit analysis; currency market; exchange rate; international trade; price dynamics; South Africa